(untitled) (Nexus International Journal of Science and Education, 2024)
The study aimed to determine the extent of system thinking-based approach and the extent of conflict management of public elementary school heads. This study employed a non-experimental quantitative research design utilizing descriptive-correlation method. Validated questionnaire and Universal sampling procedure were utilized considering the minimal number of teachers in the research locale. Two hundred fifty (250) public elementary school teachers were the respondents of the study. Using mean, pearson-r, and regression analysis, the findings revealed that the system thinking-based approach was extensive while the conflict management of public elementary school heads was also very extensive. Moreover, the overall results disclosed that indicators for the system thinking-based approach were positively related to the conflict management of public elementary school heads. Further, results from the regression analysis revealed the following have a strong influence of system thinking-based approach on the conflict management of public elementary school heads: cooperation to advance school improvement, preference, and skillset. It is recommended that the school heads should foster open communication to create channels for open and transparent communication amongst all stakeholders. Regularly communicate the school's goals, values, and progress to build mutual understanding and collaboration. It is also recommended that the school heads should establish a team of trained staff members who can mediate and resolve conflicts when they arise.